Highly Strained Heterocycles Constructed from Boron–Boron Multiple Bonds and Heavy Chalcogens. Issue 18 (30th March 2016) - Braunschweig, Holger; Constantinidis, Philipp; Dellermann, Theresa; Ewing, William C.; Fischer, Ingo; Hess, Merlin; Knight, Fergus R.; Rempel, Anna; Schneider, Christoph; Ullrich, Stefan; Vargas, Alfredo; Woollins, J. Derek
Abstract: The reactions of a diborene with elemental selenium or tellurium are shown to afford a diboraselenirane or diboratellurirane, respectively. These reactions are reminiscent of the sequestration of subvalent oxygen and nitrogen in the formation of oxiranes and aziridines; however, such reactivity is not known between alkenes and the heavy chalcogens. Although carbon is too electronegative to affect the reduction of elements with lower relative electronegativity, the highly reducing nature of the B−B double bond enables reactions with Se 0 and Te 0 . The capacity of multiple bonds between boron atoms to donate electron density is highlighted in reactions where diborynes behave as nucleophiles, attacking one of the two Te atoms of diaryltellurides, forming salts consisting of diboratellurenium cations and aryltelluride anions. Abstract : Heavy heterocycles : The reaction of diborenes with Se and Te resulted in the formation of diboraseleniranes and diboratelluriranes, while the reaction of diborynes with diarylditellurides yielded diboratellurirenium cations with aryltelluride anions. Such reactions are unique to boron–boron multiple bonds because of their reducing nature and the relatively low electronegativity of boron.